'The most important event in IWY': Freda Brown and the World Congress for International Women's Year. Issue 1 (2nd January 2020) - Milner, Lisa
Abstract: In a book for young adults on women who made Australian history, Australian political activist Freda Brown's entry includes the passing note that 'in 1975 Brown played a key role in Australia's celebration of the United Nations International Women's Year'. Until recently, there has been little acknowledgement of Brown's work in the making and marking of 1975 as International Women's Year, through her leadership of national and international women's organisations. The decision taken by the United Nations to mark 1975 as International Women's Year originated from the Women's International Democratic Federation (WIDF), a 200-million-member organisation that Brown was to lead for many years. This article examines the 1975 Berlin Congress of Women, the event that Brown and WIDF organised to mark International Women's Year, from an Australian perspective.